Endogenous Economic Growth with Education Subsidies - Zhang, Wei-Bin (International Journal of Emerging Trends in Social Sciences, 2018)
The purpose of this study is to examine existence of business fluctuations in a growth model of endogenous wealth and human capital with government’s subsidy policies on education by Zhang (2016). Zhang synthesized the Solow growth model and the Uzawa-Lucas two-sector model and took account of three ways of accumulating human capital: learning by producing, learning by education, and learning by consuming. This paper generalizes Zhang’s model by allowing all the time-independent parameters to be time-dependent. It examines the relationship between growth and taxation with different time-dependent exogenous shocks. We simulate the model to demonstrate existence of equilibrium points, motion of the dynamic system, and oscillations due to different exogenous shocks.